Potrzeba humanizacji psychiatrii w świetle pism Antoniego Kępińskiego - Kania, Witold (Śląskie Studia Historyczno-Teologiczne, 2014)
This paper shows the original humanistic approach toward the patient presented in the writings and in the example of the life of Antoni Kępiński, one of the best Polish psychiatrists of the XX century. In the beginning, the article describes Kępiński´s holistic approach toward the patient who should be treated not as a mere object of natural science. The second part focuses on Kępiński’s original therapeutic method based on axiology which his followers named “corrective axiological experience”. The last part discusses the doctor-patient relationship. According to Kępiński, a doctor should be authentic, and avoid putting on a mask and judging the patient, who is suffering and expecting to be helped.